Telemedicine vs. In-person Preoperative Appointments in Elective Orthopaedic Surgery. Issue 2 (15th December 2021) - Karamian, Brian A.; Toci, Gregory R.; Mao, Jennifer Z.; Ju, Derek G.; Canseco, Jose A.; Lambrechts, Mark J.; Hameed, Daniel; BS, BS; Grewal, Lovy; Kaye, I. David; Hilibrand, Alan S.; Kepler, Christopher K.; et al.
No abstract available